Summary of proceedings: 5th Stranded Assets Forum at Waddesdon Manor, 15th April 2016 - Kruitwagen, L; Harnett, E; Caldecott, B (Smith School of Enterprise and the Environment, 2016)
The University of Oxford's Smith School of Enterprise and the Environment and The Rothschild Foundation held the fifth Stranded Assets Forum at Waddesdon Manor, Buckinghamshire, on the 15th April 2016. The Forum examined ultra high-net-worth individuals (UHNWIs), the advice they receive on sustainable investment topics, and how they could shape demand for and the practice of sustainable investment. This report provides a summary of the proceedings and deliberations from the Forum. It outlines the key discussion points and issues that emerged during the sessions held.